VISUAL CONTENT ANALYSIS OF JAPAN’S HALAL TOURISM - Sukmayadi, Vidi; Effendi, Ridwan (IJECA (International Journal of Education and Curriculum Application), 2018)
Even though Japan is located by a great distance from Islamic countries, halal tourism prominence has become a rapidly growing interest of the country. In fact, in 2016, Japan won the ?World?s Best Non-OIC Emerging Halal Destination.? The study attempts to describe an examination of the images found in Japan?s tourism promotional brochures. The study aimed at interpreting the denotative and connotative messages of the promotional images in the sampled brochures. A visual content analysis was applied to interpret the brochures? layout and the promotional images. The findings of the study imply that distinctive Islamic Symbols and Japanese monumental structure are the prominent denotative elements of the brochure. Regarding the connotative elements, the analysis indicates that female Muslim and Halal food become the main Synecdoche in representing Japan?s Halal destination image.